Economic Feasibility Analysis of PT Trigunapratama Abadi's Hazardous Waste Processing and Collection Activities - Latifah Istiqomah; Syifa Pramudita Faddila; Ery Rosmawati (Enrichment : Journal of Management, 2022)
PT Triguna Pratama Abadi is a company that manages and destroys hazardous and toxic B3 waste. In addition, the company also produces B3 waste, for example paper-producing waste that is used as scrap paper for egg holders and contaminated soil waste into red bricks, not only that this company is also a medical waste destruction company whose scope can be from outside the city of Karawang. This business feasibility analysis activity is one of the efforts in providing alternative policies for processing and collecting B3 waste. The purpose of this study is to determine whether or not a company is feasible. With descriptive research methods and literature, the results of the analysis of the economic feasibility of processing activities are as follows, NPV Rp. 239.029 million, IRR 183% B/C value 14.28 and PBP 2 years. And the analysis of the economic feasibility of collecting activities is obtained as follows, NPV Rp. 445.269 million , IRR 238% B/C value 1.61 and PBP 7 years. With these results, a decent result is obtained in the economic activities of B3 waste management and collection at PT Triguna Pratama Abadi.